[Rezension von: Graziano, Michael, Errand into the wilderness of mirrors] - Dowland, Seth (A journal of church and state, 2023)
This creative study of the CIA’s "religious approach" to fighting the Cold War joins a growing body of scholarship examining the intersection of religion and foreign affairs. In seven tightly argued chapters, Michael Graziano charts the development of a "world religions paradigm" in both the academy and the United States’ intelligence services from WWII through Vietnam. This paradigm led CIA officers, State Department officials, and US presidents to view "religion" as an ally in the Cold War, even as it obscured the nuances and contexts that shaped the religious worlds of people around the globe. The Iranian revolution shattered the religious models that intelligence operatives had spent three-plus decades constructing.